Proposal of appication of CRM theory in productive and commercial units of clothing industry sector in the comercial emporium gamarra, in Lima - Peru (Journal of Business, Universidad del Pacífico (Lima, Peru), 2010)
Social transformations, the evolution of science and technology, globalization and modern conceptions of management that are taking place in the twenty-first century require all organizations in the world to innovate according to this new reality. “Plaza Gamarra” cannot be oblivious to these changes and requires confronting this reality, adapting organizational, administrative and functionally to new challenges. The micro and small enterprises, located in “Plaza Gamarra”, evidenced by its constant concern through its orientation to the diverse needs of consumers, their creative capacity to respond to the rapidly changing environment and technological innovationcapacity, allowing respond to the demands of the domestic and foreign markets. This research tries to guide the implementation of CRM theory in “Plaza Gamarra”, in response to the growing need for production and commercial units strengthen customer relationships, to rethink traditional concepts of marketing and use concepts of relational marketing. This decision was made after analysing several possibilities. Finally, we faced the challenge of developing this paper that we consider of great scope in a dynamic sector of the economy that can be a source of accumulation of wealth, life quality improvement and transcendence as a country.
Keywords: Micro-Enterprise; Small Enterprise; Relational Marketing; Marketing; Perception; Satisfaction; Strategies; Micro Segmentation; Value; Costumer; Production and Commercial Units; Plaza Gamarra; CRM